2011
DOI: 10.1128/jcm.02022-10
|View full text |Cite
|
Sign up to set email alerts
|

Case of Mycobacterium marinum Infection with Unusual Patterns of Susceptibility to Commonly Used Antibiotics

Abstract: Mycobacterium marinum, found commonly in salt water and freshwater, is the causative agent of disease in many species of fish and occasionally in humans. MICs to most antimicrobial agents are relatively low. Susceptibility testing is not routinely performed, and single-drug therapy is used for the treatment of most infections. Here, we report an infection caused by a drug-resistant M. marinum strain in an otherwise healthy patient. CASE REPORTA 45-year-old healthy man sought medical care following a fish hook … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…We previously described unusual resistance patterns in bacteria implicated in wound infections in patients seen within our hospital network (Parrish, Luethke, Dionne, Carroll, & Riedel, ). The infections were related to recreational activities on the Chesapeake Bay waters.…”
Section: Introductionmentioning
confidence: 99%
“…We previously described unusual resistance patterns in bacteria implicated in wound infections in patients seen within our hospital network (Parrish, Luethke, Dionne, Carroll, & Riedel, ). The infections were related to recreational activities on the Chesapeake Bay waters.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is no consensus on definitive treatment regimens due to paucity of controlled trials [3]. However, most isolates are resistant to isoniazid and pyrazinamide and produce β -lactamase [3, 10]. …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown effective eradication with a single antibiotic for uncomplicated cases, although most experts recommend 2-drug therapy [3, 10]. Clarithromycin alone, or in combination with ethambutol or rifampin, is preferred for superficial infections [2, 10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations